Express the following linear equations in the form ax + by + c = O and indicate the values of a, b and c in each case:
(i)-2x+3y=6
(ii)x=3y
(iil) 2x=-5y
(iv)y-2=0
(v)5 = 2x
Answers
Step-by-step explanation:
To express the following linear equations in the form ax + by + c = 0 and indicate the values of a, b and c in each case:
(i)-2x+3y=6
Answer:
-2x+3y-6=0
or
2x-3y+6=0
here a=2,b=-3,c=6
(ii)x=3y
Answer:
x-3y+0=0
here a=1,b=-3,c=0
(iii) 2x=-5y
Answer:
2x+5y+0=0
here a=2,b=5,c=0
(iv)y-2=0
Answer:
0.x+y-2=0
here a=0,b=1,c=-2
(v)5 = 2x
Answer:
-2x+0.y+5=0
or
2x-0.y-5=0
here a=2,b=0,c=-5
Hope it helps you.
Answer:
i) a = -2, b = 3 and c = -6
ii) a = 1, b = -3 and c = 0
iii) a = 2, b = 5 and c = 0
iv) a = 0, b = 1 and c = -2
v) a = 2. b = 0 and c = -5.
Step-by-step explanation:
In the question,
i) -2x + 3y = 6
To write it in the form of ax + by + c = 0
(-2)x + (3)y - 6 = 0
On comparing we get,
a = -2, b = 3 and c = -6
ii) x = 3y
To write it in the form of ax + by + c = 0
(1)x + (-3)y + (0) = 0
On comparing we get,
a = 1, b = -3 and c = 0
iii) 2x = -5y
To write it in the form of ax + by + c = 0
(2)x + (5)y + (0) = 0
So,
a = 2, b = 5 and c = 0
iv) y - 2 = 0
To write it in the form of ax + by + c = 0
(0)x + (1)y + (-2) = 0
So, on comparing we get,
a = 0, b = 1 and c = -2
v) 5 = 2x
To write it in the form of ax + by + c = 0
(2)x + (0)y + (-5) = 0
On comparing we get,
a = 2. b = 0 and c = -5.